Salidroside attenuates endothelial cellular senescence via decreasing the expression of inflammatory cytokines and increasing the expression of SIRT3. (October 2018) - Xing, Sha-Sha; Li, Jian; Chen, Lin; Yang, Ya-Fei; He, Ping-Lin; Li, Jun; Yang, Jin
Highlights: Hyperhomocysteinemia is an independent risk factor for various vascular diseases. Several clues suggested that salidroside has therapeutic potential on homocysteine-related cardiovascular diseases. However, the underlying molecular mechanism is still under investigation. Two observations are of enormously importance in our study. First, SAL alleviated the expression of p16 INK4A and p21 CIP1 both in aorta and in HUVECs, possibly through decreasing the expression of inflammatory cytokines and upregulating the expression of SIRT3. Second, SAL attenuated the VSMCs proliferation and collagen deposition. These information are valuable for us to understand the protective effect of SAL on vascular, though the detailed underlying molecular mechanisms still need further investigation. Abstract: Objective: Endothelial cellular senescence is an important contributor to the endothelial dysfunction and atherosclerosis. Our previous studies suggested that salidroside (SAL) can alleviate atherosclerosis and protect endothelial cells against oxidative stress induced damage. However, the effect and mechanism of SAL on endothelial cellular senescence is still unclear. Here, we investigated the underlying mechanisms of SAL on preventing endothelial cellular premature senescence. Methods and results: We established a hyperhomocysteinemia (HHcy)mouse model via high methionine diet (HMD) to explore the protective effect of SAL. According to our results, the HMD elevated the concentration of serum homocysteine. HHcy induced the collagen deposition and the up-regulation of senescence markers, i.e. p16 INK4A and p21 CIP1, in intima-medial of aorta. In addition, SAL also inhibited the expression of CD68 and intercellular adhesion molecule 1 (ICAM1) in aorta. In senescent human umbilical vein endothelial cells (HUVECs) induced by H2 O2, SAL treatment alleviated the expression of p16 INK4A and p21 CIP1 and reduced the activity of senescence-associated (SA)-β-gal. Conclusion: our data suggested that SAL decreased the expression of inflammatory cytokines and up-regulated the expression of SIRT3, which might be the underlying mechanism of SAL on preventing endothelial cells from premature senescence.